"Well, I'm going to have a baby": Navigating Safety, Stakeholders, and Strategy in Workplace Pregnancy Disclosures. Issue 4 (4th July 2022) - Billotte Verhoff, China; Buzzanell, Patrice M.
ABSTRACT: This study explores how 92 women disclosed their pregnancies in the workplace. Examining workplace pregnancy disclosure broadly rather than taking a dyadic approach (e.g. employee to supervisor) highlighted tensions and outcomes associated with simultaneously navigating disclosures to multiple colleagues and supervisors. Data analysis revealed four themes: (b) timing safely, (c) diffusing selectively, (d) controlling gatherings, and (e) crafting conversational tones. Findings situate workplace pregnancy disclosure as a dynamic multi-stakeholder process. Women's accounts suggest that risk is understood as linked to potential future disclosures and the importance of emotion in crafting disclosure interactions.